Position, Transportation, and Resources: Japan's Potential and Strategic Choices Under Analytical Geopolitics - Morgado, Nuno; Hosoda, Takashi (European Journal of Geography, 2025)
Japan is a very poor country in terms of natural and mineral resources. Consequently, it remains heavily dependent on maritime transportation. Japan’s proximity to a competing China, the ever-strengthening Sino-Russian partnership, and an aggressive North Korea constitute a hostile regional environment. This article offers an in-depth analysis of Japan’s capabilities (i.e., potential), predominantly demonstrating the weaknesses of the country. We argue that the flaws associated with Japan’s potential can be explained by both (i) geomisguided Japanese geopolitical agents, and (ii) the Japanese pacifist strategic culture. We deductively apply the model of analytical geopolitics. Our findings are that Japanese geopolitical agents are “geomisguided” as they have pursued policies of insufficient stockpiling and disregarded Japan’s dependence on the sea lanes of communication. Furthermore, Japanese public opinion does not sufficiently grasp the current threats Japan faces, and this fact limits the capacities of Japanese geopolitical agents. The paper addresses a gap in the literature by applying an innovative methodological analytical approach. Highlights: Japan is heavily dependent on maritime transportation, and the number of Japanese-flagged vessels is insufficient. Japanese maritime currents have a military impact concerning floating mines. Postwar Japanese pacifism clashes with security imperatives and encourages weaknesses in Japan’s potential.